Skrining pranikah untuk pencegahan thalassemia mayor yang efektif dan efisien. - Danang Kastowo; Alif Syaiful Huda; Andy Saputra; Erna Setyowati (JNANALOKA, 2021)
Thalassemia is a hereditary disease that cannot be cured and requires continuous blood transfusion for major sufferers. The main preventive measure of thalassemia is to identify carriers of the trait and prevent the birth of another thalassemia major baby. Inferential data analysis, with data sampling on the total population (data of patients with thalassemia major) and used to draw a conclusion. The research method used is a quantitative method, namely by counting the number of patients with thalassemia major in Indonesia, then grouping based on marital status, age of the patient, and health insurance services that have been used. The results showed that thalassemia major patients at the age of ready to marry (20-30 years old) were still very high, so premarital screening activities needed to be carried out to prevent the decline of thalassemia major in children.